Dampak Bermain Gamelan pada Peningkatan Konsentrasi Belajar Siswa Usia Sekolah Dasar di Laboratorium Seni Purwasaba Malang - Rofiqoh Firdausi; Ratna Fajarwati Meditama; Nur Al Maida; Nida Mukhlishotul ‘Izzah (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
This study aims to describe the impact of gamelan playing activities on improving the concentration of elementary school students. The study was conducted at the Purwasaba Art Laboratory in Malang using a qualitative approach and descriptive methods. The subjects of the study consisted of eight students aged 7–12 years who actively participated in gamelan activities regularly. Data were collected through observation, interviews, and documentation, then analyzed thematically. The results showed that playing gamelan had a positive impact on students' cognitive aspects, especially in increasing focus duration, learning resilience, and decreasing distractive behavior. Structured and collaborative musical activities in gamelan have been shown to train attention regulation and increase students' learning motivation. These findings indicate that traditional music can be used as an alternative effective learning strategy in supporting the development of concentration in elementary school children.